ChemInform Abstract: A Highly Efficient Method for the Synthesis of Novel 1′H‐Spiro[indene‐2, 2′‐quinazoline]‐1, 3, 4′(3′H)‐trione Derivatives. Issue 15 (24th March 2016) - Sadat‐Ebrahimi, Seyed Esmail; Irannezhad, Soroor; Moghimi, Setareh; Yahya‐Meymandi, Azadeh; Mahdavi, Mohammad; Shafiee, Abbas; Foroumadi, Alireza
Abstract: The title compounds are prepared by reaction of ninhydrin with aminobenzamides in moderate to good yields using ferric chloride as catalyst.